Comprehensive analysis of the correlation between base‑excision repair gene SNPs and esophageal squamous cell carcinoma risk in a Chinese Han population - Pu, Yu; Zhao, Liang; Dai, Nan; Xu, Mingfang (Molecular and clinical oncology, 2020)
This study sought to assess the relationship between single nucleotide polymorphisms (SNPs) affecting DNA base-excision repair (BER) genes and esophageal squamous cell carcinoma (ESCC) risk in a Han Chinese population. Genes screened for such SNPs included 8-oxoguanine DNA glycosylase (OGG1), apurinic/apyrimidinic endonuclease 1 (APE1) and X-ray repair cross-complementing group 1 protein (XRCC1). Blood samples that had been collected in a prospective manner were used for DNA extraction, with all DNA samples then being subjected to PCR-restriction fragment length polymorphism genotyping for BER gene SNPs, including APE1 Asp148Glu and -141T/G, OGG1 Ser326Cys, and XRCC1 Arg399Gln. The relationship between these SNPs and ESCC risk was then assessed, with the comparability of the case and control groups being enhanced via propensity score matching (PSM). This study initially included 642 healthy controls and 321 ESCC patients, with PSM optimization leading to a final analyzed total of 311 matched subjects per group (311 total). Factors associated with elevated ESCC risk in this analysis included advanced age, being male and smoking. We further identified that the XRCC1 399 Gln/Gln genotype was associated with a significant reduction in ESCC risk prior to propensity matching (odds ratio=0.48; 95% CI: 0.23-1.00; P<0.05), although this did not remain true following matching. For the remaining analyzed SNPs, no significant associations between genotype and ESCC risk were detected prior to or following propensity matching. A multivariate analysis incorporating patient age, sex, smoking status and drinking status failed to detect any relationship between the four tested genotypes and ESCC risk. In conclusion, being male, a smoker or of advanced age was associated with an elevated ESCC risk. However, we did not detect any significant relationship between ESCC risk and BER polymorphisms in XRCC1, OGG1, APE1 or the APE1 promoter region in a Han Chinese population.